Designing an Intrinsic Motivation model for the Teachers (Case Study: Teachers in the Department of Education in the city of Isfahan) - Hamideh Sadat Hosseini; Ali Nasr Esfahani; Ali Safari (رویکردهای نوین آموزشی, 2024)
Learning is a complex process and intrinsic motivation is one of the most effective factors in teachers' performance and students' learning. It was attempted in the present study to recognize and consider this effective factor in the Department of Education by identifying effective factors on intrinsic motivation and its variables. This is a functional study through a mixed approach and the teachers in the department of education in the city of Isfahan are the statistical population of the study which continued in the qualitative part through purposive sampling and until reaching the saturation point of the interviews. The stratified random sampling appropriate to the sample size was used in the quantitative part. The results in the qualitative part revealed positive and negative effective factors, intrinsic motivation outcomes, and their aspects. The results of the quantitative part showed that positive organizational factors, positive management factors, positive external-organizational factors, negative organizational factors, and negative management factors significantly affect intrinsic motivation with 55%, 39%, 56%, 43%, and 39% respectively. Moreover, intrinsic motivation significantly affects organizational outcomes at 65% and personal outcomes at 64%.IntroductionIntrinsic motivation is one of the most effective factors addressed in organizations since it considerably influences the staff's performance. Teachers working in the educational system are among the people whose performance is dramatically affected by intrinsic motivation. And because they are considered the most essential part of the schools and have direct communication with the students, can greatly influence the pathway of the upgrade and development of the students who bring about the future of every society; since the teachers with high intrinsic motivation increase their attempt to reach their defined purposes during the academic year.Investigating the research Literatue revealed that there is no model for intrinsic motivation in the previous studies. Moreover, there has not been any significant research regarding this important subject in the Department of Education. Hence, present study attempted to help the managers in the Department of Education recognize the reasons for the teachers' behavior and also effective factors on the considered managerial measures to improve their performance through investigating intrinsic motivation and its outcomes among the teachers. Material and Methodology It is functional in the case of purpose and descriptive-content analysis in the case of nature and method the data were collected through the survey method and it is mixed (qualitative-quantitative) in the case of method. In the qualitative part, all the expert teachers who were generally qualified and work in the department of education in the city of Isfahan and teach at Farhangian University too and know enough about the subject of the study were selected as the statistical population. Purposive sampling was used up to reaching the saturation point and the subjects were interviewed and the research model was designed according to the achieved results. All the teachers in the city of Isfahan were considered as the statistical population in the quantitative part and the sample size was calculated through a stratified sampling method appropriate to the sample size. A questionnaire was designed according to the research model by the researcher and it was administend after designing the research model. Discussion and ResultsAfter reviewing the findings in the qualitative part of the study, the components such as alignment of the teachers' purposes with education, respect, and dignity in the working environment, interesting working environment, suitable promotion system, intimate relationship with the colleagues and the teachers' mental hygiene were achieved and these components were categorized as the organizational factors which positively influence the intrinsic motivation. The next identified group includes being recognized by the superior, perceived organizational support, constructive working competition, and the manager's empowering behavior which were grouped as the managerial factors that positively influence the intrinsic motivation. The other category, too, includes the positive attitude of the society toward the job and respect, and social standing which were categorized as the managerial factors that positively influence the intrinsic motivation. Other than these components, some other factors were also identified that negatively influenced intrinsic motivation which include not giving a realistic image of the job, undesirable performance evaluation system, the incongruity between the job and the employed, and organizational injustice which were categorized as the organizational factors which negatively influence the intrinsic motivation. The other group was identified as the managerial factors that negatively influence intrinsic motivation and it includes inappropriate education, lack of participation in organizational decision-making and not operationalizing the managers' promises. In addition, the components including intrinsic motivation and its outcomes were also identified as constant growth,  performance improvement, and instructive working environment were categorized as the outcomes related to the organization; and innovation and creativity, consciousness, occupational achievement, organizational citizenship behavior, vocational competence, positive effects of the job on the teachers' lives, more attempt, receiving positive feedback from the students and parents, having effective communication with the students and sharing knowledge and experience were categorized as the related outcomes to the individual. The significant effect of all the identified factors on each other was investigated in the quantitative part.ConclusionIt was attempted in the present study designed a model for the teachers' intrinsic motivation and then through quantitively investigating the identified factors in the present study, the type of relationship between the identified components was investigated too and it was revealed that great steps can be taken in the educational system and dramatic changes can be made through reinforcing intrinsic motivation and considering effective factors on it.